Mempelajari Proses Produksi Wire Harness Dan Studi Kasus Serta Perawatan Pada Mesin Cheker KCM Di CV. HIJ - Anantha Malden; Kardiman Kardiman; Marno Marno; Nanang Burhan (TRAKSI, 2021)
Wire harness is one of the most important components in two-wheeled and four-wheeled vehicles which functions to transmit electric current and signals to motorized vehicles. CV. HIJ is a company engaged in the automotive sector. This company produces various types of wire harnesses for several companies in Indonesia. The checker machine is a tool used to check electric currents and signals.The checker machine is a very important step in the wire harness manufacturing process.Based on the background, this research focuses on the flow of the wire harness productionprocess, the checker machine to study the repair and maintenance of the checker machine, and to find the cause and effect on the checker machine pins using the fishbone diagram method. The function of the fishbone diagram aims to find the cause andeffect of the broken pin experienced in the checker machine. The analysis uses 4 of the 6 main factors, because there are only 4 factors that affect the process of checking thewire flow. The cause of a broken pin there are 4 factors, namely: material, machine, method, and human. Of the 4 factors that affect pin pata the most, humans are caused by lack of training and poor behavior at work.Checker machine at CV. HIJ has 10 preventive daily maintenance or preventive maintenance. Preventive maintenance at the company has not been used optimally and there is an additional point according to the author, namely how to enter the pin correctly.Aims to minimize damage to the checker machine.